Exploring the components of physician volunteer engagement: a qualitative investigation of a national Canadian simulation-based training programme. Issue 6 (23rd June 2017) - Sarti, Aimee J; Sutherland, Stephanie; Landriault, Angele; DesRosier, Kirk; Brien, Susan; Cardinal, Pierre
Abstract : Objectives: Conceptual clarity on physician volunteer engagement is lacking in the medical literature. The aim of this study was to present a conceptual framework to describe the elements which influence physician volunteer engagement and to explore volunteer engagement within a national educational programme. Setting: The context for this study was the Acute Critical Events Simulation (ACES) programme in Canada, which has successfully evolved into a national educational programme, driven by physician volunteers. From 2010 to 2014, the programme recruited 73 volunteer healthcare professionals who contributed to the creation of educational materials and/or served as instructors. Method: A conceptual framework was constructed based on an extensive literature review and expert consultation. Secondary qualitative analysis was undertaken on 15 semistructured interviews conducted from 2012 to 2013 with programme directors and healthcare professionals across Canada. An additional 15 interviews were conducted in 2015 with physician volunteers to achieve thematic saturation. Data were analysed iteratively and inductive coding techniques applied. Results: From the physician volunteer data, 11 themes emerged. The most prominent themes included volunteer recruitment, retention, exchange, recognition, educator network and quasi-volunteerism. Captured within these interrelated themes were the framework elements, including the synergistic effects of emotional, cognitive and reciprocal engagement. Behavioural engagement was driven by these factors along with a cue to action, which led to contributions to the ACES programme. Conclusion: This investigation provides a preliminary framework and supportive evidence towards understanding the complex construct of physician volunteer engagement. The need for this research is particularly important in present day, where growing fiscal constraints create challenges for medical education to do more with less.